2001
DOI: 10.1159/000049493
|View full text |Cite
|
Sign up to set email alerts
|

A Hypoallergenic Derivative of the Major Allergen of the Dust Mite <i>Lepidoglyphus destructor</i>, Lep d 2.6Cys, Induces Less IgE Reactivity and Cellular Response in the Skin than Recombinant Lep d 2

Abstract: Background: The major allergen of the dust mite Lepidoglyphus destructor, Lep d 2, has been produced as a recombinant allergen (rLep d 2) with IgE reactivity both in vivo and in vitro. A modified form of rLep d 2 (rLep d 2.6Cys) obtained by site-directed mutagenesis has been shown to have a reduced IgE reactivity in vitro. In this study we have compared the ability of rLep d 2 and rLep d 2.6Cys to elicit positive skin prick tests and cellular responses among L. destructor-sensitized subjects. Methods: Seventee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Hypoallergens displaying a decreased IgE-binding activity and a conserved T cell reactivity were generated for the nonspecific lipid transfer protein Par j 1 from P. judaica pollen [85] and the major latex allergen Hev b 6.02 [86]. Disulfide bonds present in the group 2 allergens of mites were also destroyed by site-directed mutagenesis to destabilize the antigenic structure and ablate IgE binding of Der p 2 [87], Der f 2 [88], and Lep d 2 [89,90]. …”
Section: Vaccine Developmentmentioning
confidence: 99%
“…Hypoallergens displaying a decreased IgE-binding activity and a conserved T cell reactivity were generated for the nonspecific lipid transfer protein Par j 1 from P. judaica pollen [85] and the major latex allergen Hev b 6.02 [86]. Disulfide bonds present in the group 2 allergens of mites were also destroyed by site-directed mutagenesis to destabilize the antigenic structure and ablate IgE binding of Der p 2 [87], Der f 2 [88], and Lep d 2 [89,90]. …”
Section: Vaccine Developmentmentioning
confidence: 99%
“…Disulfide bonds stabilizing the antigenic structure of major allergens of house dust mites were also targeted by site-directed mutagenesis. Hypoallergenic variants of Der p 2 [54], Der f 2 [55], and Lep d 2 [56,57] were produced and evaluated for their IgEmediated reactions and cellular responses. One potential problem when targeting the conformation of allergens could be the solubility of the final product, as denatured or unfolded proteins tend to form aggregates.…”
Section: Site-directed Mutantsmentioning
confidence: 99%
“…Interestingly, mutation of the cysteines stabilizing two smaller loops had even larger effects and reduced the allergenicity100-fold. Similar strategies for the homologous allergens from Lepidoglyphus destructor [3] and D. farinae [4] produced a loss of allergenicity and the retention of the ability to stimulate T-cell responses from peripheral blood mononuclear cells (PBMC). Further study on the Der f 2 showed that the mutants could reduce the induction of airway hyperreactivity in mice [5].…”
Section: Mutation Of Disulphide Bondsmentioning
confidence: 99%